Evaluation size and number of yellow potato tubers under different planting densities using zero-inflated models - Bernal-Margfoy, Nelson; Darghan, Enrique; Rodríguez, Luis; Gonzalez, German (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
A field study was carried out on the cultivation of the yellow diploid potato (Solanum tuberosum Phureja Group) to evaluate the influence of the planting density associated with distances between plants of 30, 40, and 50 cm and distances between the rows and paths of 100 cm on the tuber count with sizes less than 2 cm, 2-4 cm, 4-6 cm, and more than 6 cm. At the time of the harvest of the tubers, they were classified by size and respective count was made. The modelling of the counts was done by means of the usual negative binomial regression and by the inflated zeros option. The zero-inflated negative binomial regression models showed a significant effect of the sowing density on the tuber count in the sizes that were superior to 4 cm while the negative binomial model showed a significant effect it in the case of the sizes lower than 4 cm. The results on size and density are attributes of interest in both the agronomic management of this crop and in the industrial management of the tubers, so the relationship that we found can be adopted in both areas to generate the desired attributes of the crop for improving the production and guiding the process of industrialization.